Culture and Psychopathology: New Perspectives on Research, Practice, and Clinical Training in a Globalized World - Moleiro, Carla (Frontiers in Psychiatry, 2018)
The present paper discusses the role of culture in understanding and treating psychopathology. It describes new perspectives on the conceptualization of psychopathology and on the definition of culture, and how these are intertwined. The impacts of culture, explicit and implicit discrimination, and minority stress on mental health are reviewed, especially in the current era. Culturally-sensitive assessment practices in psychopathology are emphasized, including addressing the multiple cultural identities of the patient, the explanatory models of the experienced distress, specific psychosocial stressors and strengths, and the cultural features of the practitioner-patient relationship in the clinical encounter. The particular case of psychotherapy in working with culturally diverse patients is explored. Finally, mainstreaming of culture in research and clinical training in psychopathology is highlighted, acknowledging that each clinical interaction is a cultural one.